Hubungan Penerapan Best Management Practice Pengolahan Karet Remah Pada Kinerja Pemasaran PT. Remco Rubber Indonesia - Afsyas Mustakim; Suharno; Burhanuddin (Forum Agribisnis, 2023)
Rubber is a cultivated plant that plays an important role in economic activities in Indonesia, which is a source of national income besides oil and gas. Most of the semi-finished natural rubber production in Indonesia is crumb rubber, especially crumb rubber with the SIR 20 standard. Best Management Practice is a standard method or reference in increasing the yield and quality of production of a commodity which also increases product marketing and income of companies or plantations that implement it. The purposes of this research were to: (1) analyze the marketing results before and after the implementation of BMP in PT. Remco Rubber Indonesia and (2) analyzing the crumb rubber marketing strategy implemented by PT. Remco Rubber Indonesia. The research method used is paired t-test analysis and 4P marketing mix strategy analysis. The results of the t-test using SPSS 26 showed that the marketing of crumb rubber at PT. Remco experienced a significant increase after the application of BMP in the crumb rubber processing. For the marketing mix strategy implemented at PT. Remco has been well implemented. This means that the application of BMP in crumb rubber processing has a significant relationship in implementing marketing strategies in increasing marketing.